Drug repurposing: potential of Antimicrobial Drugs in Breast Cancer Treatment - Chakraborty, Anuradha (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.